Ultrasound Technology in the Diagnosis and Prognosis of Mastitis in Dairy Cattle: Advancements, Applications, and Future Directions - Abdul Mateen,; Aslam, Sadaf; Muhammad Abdullah, Obaid; Qaisrani, Sajid Ali; Abdul Aziz,; Sajid, Sajid Mahmood; Mohi Ud Din, Abrar; Khalique, Mubashir Ali; Ahmed, Gulzar (Indus Journal of Bioscience Research, 2025)
The review article examines the pivotal importance of ultrasound technology in the diagnosis and prognosis of mastitis in dairy cattle, a prominent obstacle in the dairy business. Mastitis, a condition characterised by inflammation of the mammary gland, carries significant economic and animal welfare consequences, underscoring the importance of prompt and precise care. Ultrasound, being a non-invasive and adaptable imaging technology, has become a potent diagnostic and prognostic aid. The article discusses mastitis, its financial ramifications, and the imperative nature of timely detection. The text explores the evolution of ultrasonic technology, examines its utilisation in veterinary care, and emphasises its advantages over conventional techniques. Furthermore, it explores the prognostic elements, namely in forecasting milk production and udder-related ailments. This text provides an explanation of how mastitis can be assessed using digital image analysis, numerical pixel values, and pixel heterogeneity. The article discusses the utilisation of real-time monitoring technology and the incorporation of artificial intelligence in the analysis of ultrasound data. The statement recognises the difficulties in using ultrasonography on a large scale and supports further investigation and practical application of this technology. In essence, it sees ultrasound as a highly promising instrument for enhancing the health and productivity of dairy cattle.